Network Method Critical Path as a search problem solvers Critical Path - Fachrudin Fachrudin (Jurnal Sistem Informasi, 2005)
Activity is a lot of work takes time, energy and capital. Many companies do a lot of unplanned activities with a working method so that his workers are not finished just because time. This is much work other jobs to do and finished at the same time while a job with another job different in kind. Of the things mentioned above then the writing will be presented a solution that can solve problems with a method, the method known as Network or Network Method, The Critical Path Method as a search problem solvers and critical path settings. With this method is expected to work in a lot of companies will be completed on time, so that will create a company work efficiency.